2017
DOI: 10.1371/journal.pntd.0006065
|View full text |Cite
|
Sign up to set email alerts
|

Review of the factors influencing the motivation of community drug distributors towards the control and elimination of neglected tropical diseases (NTDs)

Abstract: BackgroundCommunity drug distributors or neglected tropical disease (NTD) volunteers have played a crucial role in ensuring the success of mass drug administration (MDA) programs using preventive chemotherapy (PC) for lymphatic filariasis, onchocerciasis, schistosomiasis, trachoma and soil transmitted helminths. In recent years however, a noticeable decline in motivation of some of these volunteers has been perceived, potentially negatively impacting the success of these programs. Potential hypotheses for this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
79
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(89 citation statements)
references
References 60 publications
(130 reference statements)
10
79
0
Order By: Relevance
“…A conceptual framework mapping out the key components of community-wide MDA was developed as a tool to shape the codebook and coding process. Development of the framework was based on existing literature and authors' implementation experience regarding delivery of MDA programs [14][15][16][17]. The framework (Fig 1) presents key inputs and contextual factors relevant to the planning and delivery of MDA leading to two outputs: "reach" and "uptake".…”
Section: Data Management and Analysismentioning
confidence: 99%
“…A conceptual framework mapping out the key components of community-wide MDA was developed as a tool to shape the codebook and coding process. Development of the framework was based on existing literature and authors' implementation experience regarding delivery of MDA programs [14][15][16][17]. The framework (Fig 1) presents key inputs and contextual factors relevant to the planning and delivery of MDA leading to two outputs: "reach" and "uptake".…”
Section: Data Management and Analysismentioning
confidence: 99%
“…While gender-related differences in terms of NTD burden are well documented, there is a paucity of research on how gender interacts with NTD service provision and uptake. Of the limited literature available, studies have mainly explored access to mass drug administration (MDA) and how gender relates to the experience of being an NTD volunteer [29][30][31][32][33][34][35][36]. For example, that female NTD volunteers uniquely contend with the challenges of balancing work and family commitments [31].…”
Section: Introductionmentioning
confidence: 99%
“…Of the limited literature available, studies have mainly explored access to mass drug administration (MDA) and how gender relates to the experience of being an NTD volunteer [29][30][31][32][33][34][35][36]. For example, that female NTD volunteers uniquely contend with the challenges of balancing work and family commitments [31]. In terms of MDA coverage, a study in Uganda found that men may miss out on treatment as they were more likely to be away from their homes due to occupational roles, whilst some Community Drug Distributors (CDDs) withheld drugs from pregnant or breastfeeding women due to drug safety concerns [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is likely due to the fact that FGD guides were not specifically designed to delve into gender-specific content. Several studies have similarly identified that male and female CDDs approach MDA delivery activities such as community sensitization differently and thus an awareness of the preferences and needs of each gender may be an important addition to CDD training activities [12,33]. A more gender-equitable CDD workforce may have a more balanced representation of the priorities and concerns of all genders, with positive effects on MDA treatment coverage.…”
Section: Discussionmentioning
confidence: 99%